2022
DOI: 10.1039/d2sc04982a
|View full text |Cite
|
Sign up to set email alerts
|

Carrier gas triggered controlled biolistic delivery of DNA and protein therapeutics from metal–organic frameworks

Abstract: The efficacy and specificity of protein, DNA, and RNA-based drugs make them popular in the clinic; however, these drugs are often delivered via injection, requiring skilled medical personnel, and producing...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…[24][25][26][27][28][29][30] Recent work has shown that the biofriendly zeolitic imidazolate framework-8 (ZIF-8)-encapsulated vaccines promote a more robust immune response against viral nanoparticles or whole-cell bacteria when injected subcutaneously. 24,25,[31][32][33] These results are striking, but in all cases, the vaccines used have been "self-adjuvanting" as the RNA or DNA within a virus or the lipopolysaccharides on the inactivated bacteria can induce their own strong immune response. Further, it is not clear what happens to the ZIF inside the skin, nor has size dependence on the toxicity of the particles in vivo been assessed as they reside for so long within the tissue.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28][29][30] Recent work has shown that the biofriendly zeolitic imidazolate framework-8 (ZIF-8)-encapsulated vaccines promote a more robust immune response against viral nanoparticles or whole-cell bacteria when injected subcutaneously. 24,25,[31][32][33] These results are striking, but in all cases, the vaccines used have been "self-adjuvanting" as the RNA or DNA within a virus or the lipopolysaccharides on the inactivated bacteria can induce their own strong immune response. Further, it is not clear what happens to the ZIF inside the skin, nor has size dependence on the toxicity of the particles in vivo been assessed as they reside for so long within the tissue.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 ZIFs are unique as polymeric materials due to their kinetic lability; phosphate and carbonate salts, or albumin-rich environments readily pull the zinc from the framework causing it to dissolve completely, returning the original antigen to its pristine state. 14,15 ZIF's versatility in capturing, preserving, and releasing antigens is exceptional and has been used to encapsulate whole viruses, 16,17 bacteria, 18 proteins, 19,20 DNA, 21,22 RNA, 23 yeast, 24 liposomes, 25,26 enzymes, 27,28 glycans, 29 and carbohydrates. 30 We have recently shown that ZIF-encapsulated formulations exhibit a depot effect, which signicantly enhances the efficacy of vaccine models.…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) are crystalline materials formed through the coordination of organic linkers to metal nodes. 1 MOFs are used in a variety of applications such as biomedicine, 2–6 catalysis, 7,8 sensors, 9–11 conductors, 12–15 gas storage and separations. 16–20 The capture and storage of CO 2 is a growing area of research.…”
Section: Introductionmentioning
confidence: 99%